2002
DOI: 10.1002/j.1556-6678.2002.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Work and Cultural Values in Occupational Choice, Satisfaction, and Success: A Theoretical Statement

Abstract: Theorists have all but ignored the career development of ethnic and cultural minorities. The purpose of this article is to rectify this oversight by presenting a values‐based theory of occupational choice, satisfaction, and success. Values were chosen as the cornerstone of the theory because work values have been identified as critical variables in the career development process (e.g., N. A. Fouad, 1995; D. E. Super & B. Sverko, 1995). Cultural values also play an important role in the occupational choice‐maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
1
25

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(231 citation statements)
references
References 57 publications
4
201
1
25
Order By: Relevance
“…According to [7]- [9] The career of parents is very much related to the careers choices of their children that parents influence, attitudes and values can strongly influence the individual choice of career and is even stronger in socialist culture due to the fact that respect for and obedience to one"s parents is often a highly prioritized value.…”
Section: Parental and Peers Influencesmentioning
confidence: 99%
“…According to [7]- [9] The career of parents is very much related to the careers choices of their children that parents influence, attitudes and values can strongly influence the individual choice of career and is even stronger in socialist culture due to the fact that respect for and obedience to one"s parents is often a highly prioritized value.…”
Section: Parental and Peers Influencesmentioning
confidence: 99%
“…In addition to familial influence on an individual's preferences for combining work and family, research shows that the occupational choices made by parents can exert a direct influence on the career choices of their children. According to (Brown, 2002), family or group influence impact both the decision-making process and the career an individual chooses. Moreover, the economic situation, especially the conditions in the labor market and the stability of employment appear to impact career choices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding supports Karibe et al's (2009) finding that people make career-related choices to meet family expectations. Brown (2002) and Mitchell and Krumboltz 12 (1996) also reported that people from collectivist families or cultures who embrace the same values tend to choose careers that meet the expectations of reference groups and that people who embrace collective social values experience career satisfaction to the extent that their chosen careers are approved by social frames of reference such as parents and peers. The extracts below support the finding that significant others influence the career-related decisions of students.…”
Section: Expectations Of Significant Othermentioning
confidence: 99%